Reinterpretasi Teks Kejadian 1:28-30 dari Perspektif Bioreginalisme dan Implikasinya bagi Krisis Ekologi - Delviero_ (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2025)
The problem of natural exploitation is currently increasingly prevalent. In addition, there is a mistake in understanding the text of the scriptures, especially the three words in Genesis 1:28-30: fill, subdue, and have dominion. These three words are often considered to be the cause of natural exploitation from a theological perspective. This background encourages the author to provide a pro-ecological interpretation of the text of Genesis 1:28-30, using a bioregionalism perspective. The research method employed in this paper is a descriptive qualitative approach, as described by Daniel K. Listijabudi's hermeneutic perspective. The results of the study indicate that, by adopting a bioregional perspective in interpreting the text of Genesis 1:28-30, the command to 'fill, subdue, and have dominion' is not an exploitative one. This command utilizes nature guided by ecological insight and is oriented to its ecological implications